AN ANALYSIS OF MORAL VALUES IN MOVIE ENCANTO - sarah, Rumi; Ikhsanudin; Rosnija, Eni (LPPM Universitas PGRI Jombang, 2025)
This study explores the moral values portrayed in the animated film Encanto. Using a qualitative approach and structural analysis based on Pavis (1998), the research examines key scenes and dialogues to identify the film’s underlying moral themes. Data were collected through close analysis of the movie’s script, focusing on character behavior and narrative structure. The findings show Encanto highlights several important moral values, including love, positivity, perseverance, resilience, and wisdom. These values are reflected through the characters’ personal struggles and family dynamics. The emotional intelligence demonstrated by the characters also presents opportunities for educators to teach emotional regulation and resilience in the classroom. As a result, Encanto can serve as an effective tool in moral education, helping students connect fictional experiences to real-life situations. This study encourages learners to reflect on ethical messages and apply them in their daily lives, contributing to their personal and social development